Norovirus outbreak among students of a boarding school in Kluang, Johor, Malaysia - Mohamad Nizam Subahir; Mohammad Saffree Jeffree; Mohd Rohaizat Hassan; Md Faizul Abd Razak; Syarifah Noor Ghulam Mohamad; Siat Yee Fong; Kamruddin Ahmed (Journal of Infection in Developing Countries)
Introduction: Norovirus (NoV) is a contagious virus causing acute gastroenteritis and is mainly responsible for diarrheal outbreak in closed settings. The aims of this study were to describe the epidemiological characteristic of an outbreak in a boarding school, to assess the extent of the outbreak and to implement appropriate control measures.